Basal cell carcinoma in the scrotal region of a young male patient: atypical presentation - Lucas S. Madureira; Julia C. K. El Dib; Vivian W. Lederman; Liz S. Gea; Paula F. M. Madureira; Eduardo C.N. Constantino (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Basal cell carcinoma (BCC) is the most common type of malignant cutaneous neoplasm, followed by squamous cell carcinoma and melanoma. Body areas most exposed to light, such as the head and neck, are most affected by BCC, due to cellular DNA damage caused by ultraviolet radiation (UVR). The effects of UVR are cumulative throughout life, explaining the higher incidence of BCC in middle-aged and elderly individuals. However, incidence has been increasing among young people, and in some cases, BCC occurs in areas typically not exposed to light. Recent findings on pathogenesis highlight the involvement of specific genetic alterations, especially in sporadic cases among young patients. Here, we report a BCC in a young patient an unusual location (scrotal skin), emphasizing the importance of thorough dermatological evaluation and considering possible alternative pathogenic mechanisms for this disease.